Vancomycin-Induced DRESS Syndrome: An Important Concern in Orthopedic Surgery - Emma Littlehales; Odhrán Murray; Robert Dunsmuir (Case Reports in Orthopedics)
DRESS (drug reaction with eosinophilia and systemic symptoms) is a potentially serious complication when prolonged courses of antibiotics are given to patients, with an average onset of 2–6 weeks after commencement. There is a high mortality rate (1–10%). We report the case of a 62-year-old male who developed DRESS after seven weeks of antibiotic treatment with vancomycin for a deep spinal metalwork infection. We describe the typical rash and biochemical results, including eosinophilia, as well as the systemic signs seen in this case. The criteria for diagnosis of DRESS, including the RegiSCAR scoring system and commonly affected systems (renal, cardiac, and hepatic), are detailed, and we also discuss evidence for steroid treatment and considerations important in the use of this.